Propierties of amylases from coffee berry borer Hypothenemus hampei (Coleoptera: Scolytidae) - MARTÍNEZ-D., CLAUDIA P.; GONZÁLEZ-G., MARÍA TERESA; BUSTILLO-P., ALEX E.; VALENCIA-J., ARNUBIO (Revista Colombiana de Entomología, 2000)
Amylase is an enzyme with high activity in the digestive system H. hampei. Its function allows the insect to actively digest the starch present in the digestive system of coffee berry borer, providing the glucose that is required to fulfill its metabolic functions. The amylolytic activity knowledge from CBB, is an essential study for inhibitors selection, which can be used for transgenic coffee production. In order to determine the best extraction solution, pH, and optimal temperature for the amylolytic activity of the insect, 1g of adult insects was pestled with different solutions containing either 5 mi of water, 1 % NaCl, or extraction buffers with different pH. Enzyme activity was determined by spectrophotometry at 580nm. An amylolytic activity zymogram was prepared using whole adults and adult intestines inhomogeneous gels 15%. The best amylase extraction solution was a solution containing 1 % NaCl. The optimal activity pH for the enzyme was 5,0 and the optimal activity temperature 40ºC. The amylolytic activity zymogram showed several activity bands. Two main bands with enzyme activity are present in the digestive system of the CBB.